PARENTAL INFLUENCE IN RANDA ABDEL-FATTAH’S DOES MY HEAD LOOK BIG IN THIS? - Insania Chlisna Violita; Sufi Ikrima Sa'adah (Universitas Negeri Surabaya, 2026)
This study examines the formation of Muslim identity in Amal, a Palestinian-Australian Muslim teenager in Randa Abdel-Fattah’s Does My Head Look Big in This? Amal has lived in Australia since she was born, raised in a spiritual family within a diasporic setting. The article further addresses the question of how Amal’s parents shape her Muslim identity within a multicultural minority-Muslim context. The analysis focuses on the parental influences on Amal’s identity formation as a Muslim who is faithful in her decision to wear hijab. This study employed a qualitative descriptive approach with textual analysis. The data were collected from narratives and dialogues in the novel that address parental influence and identity formation. The analysis is situated within postcolonial and diasporic perspectives, while Stuart Hall’s concept of cultural identity, particularly identity as “being” and “becoming,” serves as the primary analytical framework. The findings demonstrate that Amal’s parents shape her Muslim identity in three interconnected ways: as keepers of cultural roots, as providers of emotional support, and as mediators in negotiating identity within a multicultural society. These roles give Amal both cultural grounding and emotional strength to face stereotypes and discrimination. The study concludes that parental influence functions as an important foundation for maintaining cultural continuity while helping Muslim adolescents negotiate identity within multicultural diaspora contexts. The study also contributes to postcolonial and diaspora discussions by emphasizing the family as a significant site of identity formation in literary representations of Muslim minority experience.